2020
DOI: 10.1111/ctr.14044
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NLRP3 inflammasome to reduce warm ischemic injury in donation after circulatory death heart

Abstract: While the donation after circulatory death (DCD) heart transplantation is an emerging clinical practice, the primary source of donor hearts for transplantation remains donation after brain death (DBD) donors. DCD process induces formation of NOD‐like receptor family pyrin domain containing‐3 (NLRP3) inflammasome, a key mediator of inflammation‐driven damage to heart. Inhibition of NLRP3 inflammasome formation could be protective to DCD hearts. Five groups (n = 8 each) of mice were studied—control beating heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…NLRP3 inflammasome is a major mediator of inflammation-mediated damage to the DCD heart. 4 We demonstrated in our lab that NLRP3 knockout mice were protected from ischemia/reperfusion injury associated with the DCD process. 4 In the present study, we show that inhibition of NLRP3 in DCD hearts improve the function and decreased the formation of active NLRP3 inflammasome (ie, decreased ASC protein levels in DCD NLRP3-I heart tissue).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…NLRP3 inflammasome is a major mediator of inflammation-mediated damage to the DCD heart. 4 We demonstrated in our lab that NLRP3 knockout mice were protected from ischemia/reperfusion injury associated with the DCD process. 4 In the present study, we show that inhibition of NLRP3 in DCD hearts improve the function and decreased the formation of active NLRP3 inflammasome (ie, decreased ASC protein levels in DCD NLRP3-I heart tissue).…”
Section: Discussionmentioning
confidence: 92%
“… 4 We demonstrated in our lab that NLRP3 knockout mice were protected from ischemia/reperfusion injury associated with the DCD process. 4 In the present study, we show that inhibition of NLRP3 in DCD hearts improve the function and decreased the formation of active NLRP3 inflammasome (ie, decreased ASC protein levels in DCD NLRP3-I heart tissue). NLRP3 inflammasome inhibitor has been shown to be cardioprotective following acute myocardial infarction in mice.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, hydrogen gas inhalation can attenuate myocardial IRI in rats by the inhibition of oxidative stress and NLRP3-mediated pyroptosis ( Nie et al, 2021 ). Notably, Quader et al (2020) reported that the DCD procedure resulted in the activation of the NLRP3 inflammasome, which contributed to myocardial damage and dysfunction, while NLRP3 inflammasome inhibition ameliorated myocardial warm ischemia injury and improved DCD heart function. In line with the above findings, our study shows 25-min warm ischemia in the DCD hearts impairs the cardiac function of hearts during 105-min EVHP and leads to a significant increase in the level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome-mediated pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of inflammasome inhibition in DCD hearts was previously confirmed in a mice NLR family pyrin domain containing 3 knockout model. 6 Although the current study focuses on left ventricle preservation, it would be of interest to determine the effect of inflammasome inhibition on the right side of the heart. There may be differences given the distinct embryonic origins of the left- and right-side chambers being derived from the primary and secondary heart fields, respectively.…”
mentioning
confidence: 99%